Anti-inflammatory Effects of a Novel Herbal Extract in the Muscle and Spinal Cord of an Amyotrophic Lateral Sclerosis Animal Model - Lee, Sun Hwa; Cai, Mudan; Yang, Eun Jin (Frontiers in Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) is a complex disease characterized by motor neuron loss and muscle atrophy. There is no prominent treatment for ALS as the pathogenic process in the skeletal muscle and spinal cord is complex and multifactorial. Therefore, we investigated the effects of an herbal formula on the multi-target effects in the skeletal muscle and spinal cord in hSOD1G93A transgenic mice. We prepared an herbal extract (HE) from Glycyrrhiza uralensis, Atractylodes macrocephala Koidzumi, Panax ginseng, and Astragalus membranaceus. Control and herbal extract-treated mice underwent rotarod and footprint tests. We also performed immunohistochemical and Western blotting analyses to assess expression of inflammation-related and oxidative stress-related proteins in the muscle and spinal cord tissues. We found that the HE increased motor activity and reduced motor neuron loss in hSOD1G93A mice. In addition, the HE significantly reduced the levels of inflammatory proteins and oxidative stress-related proteins in the skeletal muscles and spinal cord in hSOD1G93A mice. Furthermore, we demonstrated that the HE regulated autophagy function and augmented neuromuscular junction in the muscle of hSOD1G93A mice. Based on these results, we propose the HE formula to be a possible therapeutic strategy for multi-target treatment in complex and multifactorial pathological diseases.